Taxonomia e distribuição geográfica dos Monstrilloida (Copepoda - Crustacea) do Atlântico sul ocidental - Dias, Cristina de Oliveira (2002)
Taxonomic and ecological works of the group are limited by the rarity of specimens which are captured by plankton nets as adults only. Most stages are highly modified internai parasites of benthic polychaetes and molluscs. The material examined was collected during zooplankton surveys in neritic and oceanic areas off the coast of Brazil and Argentina. The diagnostic taxonomic characteristics of the South Occidental Atlantic specimens are similar to the one found in other places. with some variations in relation to the length of the body. The pattem of antennular armature was described for each species in order to use this feature in future taxonimical comparisons. The fifteen species were associated to four areas each with distinct conditions of temperature and salinity. The following associations of monstrilloids in the surveyed area were determined by cluster analysis: a) species associations of the Tropical Zone – with species of Areas l and 2 . ln Area 1 Monstrilla grandis. M rugosa, M careli, Cymbasoma rigidum. C. longispinosum, and Monstrillopsis gracilis occurred. lt included the coast of region from Rio Grande do Norte to Alagoas (Brazil), with temperatures ranging between 27 and 37 ºC and salinity between 35.4 and 36.4 PSU. These values are characteristic of the Shelf and Tropical Waters in the region. Monstrilla brasiliensis. M. careli. M. satchmoi, M bahiana, and Monstrillopsis gracilis occurred in Area 2, restricted to coastal zone of Bahia (Brazil). with temperatures between 25.4 and 26.9 ºC and salinity between 36.4 to 3 7.4 PSU characteristic of Tropical Water: b) species association of the Subtropical Zone – it included Monstrilla grandis. i\1. careli. M. rugosa. M. brasiliensis, M. pustu/ata, M satchmoi. Cymbasoma quadridens. C. longispinosum. C. rigidum. C. rachai. Monstrillopsis dubia. M. gracilis. and M fosshageni occurred in the coastal zone from Espírito Santo to Santa Catarina (Brazil), with a thermal range of 20.5 – 29.6 ºC and a salinic variability of 28 – 35.9 PSU; these values are characteristic ofthe Shelf and Coastal Waters; and e) species association of the Transitional Zone – with Monstrilla grandis and ,\;f helgolandica. both occurred in the coasts off Argentina (12.3 to 19 ºC. 33.3 to 34 PSU. The Transitional Zone is defined as an area of mixture of Subtropical and Subantarctic Zone conditions. These is a decreasing number of species from North to South. most species are not limited to one water mass. The species recorded usually are distributed in one water mass entirely. and also in at least parts of one or two others.